The effect of financial inclusion and financial technology on effectiveness of the Indonesian monetary policy - Birgitta Dian Saraswati; Ghozali Maskie; David Kaluge; Rachmad Kresna Sakti (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The existence of non-inclusive households significantly reduces the effect of the interest rate change policy on households inter-temporal consumption decisions. Further, financial inclusion is closely related to fintech. On the one hand, fintech helps overcome the financial inclusion problem because fintech manages to reach those who were previously inaccessible by banks. On the other hand, fintech will change the payment system structure in an economy that will eventually affect the effectiveness of monetary policy. Using the Vector Error Correction Model (VECM) with the observation period of 2009-2018, this study aims to analyze the effects of financial inclusion and fintech on effectiveness of the Indonesian monetary policy within the framework of the transmission mechanism of monetary policy through interest rate channel with both the cost of capital effect and the substitution effect. The results demonstrate that financial inclusion level affects inflation rate as a proxy of effectiveness of the Indonesian monetary policy, both in the short run and long run. However, the effect of shocks in financial inclusion on inflation is not permanent. Meanwhile, fintech only affects inflation rate in the short run. However, shocks in fintech affect the volatility of inflation rate is permanent both through the substitution effect and the cost of capital effect.
Keywords: E52; 650; financial inclusion; financial technology (Fintech); inflation; transmission mechanism of monetary policy; interest rate channel; Vector Error Correction Model (VECM)